Answer:
y=1.5x+2
Step-by-step explanation:
y-y1=m(x-x1)
y-5=1.5(x-2)
y=1.5x-3+5
y=1.5x+2
Simplify the expression:
(14 - 3a) + (5a+4)
show work if u can
Answer:
(2a + 18)
Step-by-step explanation:
Rearrange Terms
(14−3)+(5+4)
(−3+14)+(5+4)
Eliminate the brackets
(−3+14)+(5+4)
−3+14+5+4
Add the numbers
−3+14+5+4
−3+18+5
Combine like terms
−3+18+5
= 2+18
need help ...........
Answer:
SAS
Step-by-step explanation:
Hope I helped!!
help me plsss i’m gonna fail lol
Answer: 5
Step-by-step explanation:
Answer:
Step-by-step explanation:
17.7... i think
Is the given value a solution to the equation? 4(n) - 3 = -2(n) + 9 n=2
Answer:
Yes!
The solution to the equation is n = 2
Step-by-step explanation:
Given the equation
[tex]4\left(n\right)-3=-2\left(n\right)+9[/tex]
remove the parentheses
[tex]4n-3=-2n+9[/tex]
Add 3 to both sides
[tex]4n-3+3=-2n+9+3[/tex]
Simplify
[tex]4n=-2n+12[/tex]
Add 2n to both sides
[tex]4n+2n=-2n+12+2n[/tex]
Simplify
[tex]6n=12[/tex]
Divide both sides by 6
[tex]\frac{6n}{6}=\frac{12}{6}[/tex]
Simplify
[tex]n=2[/tex]
Therefore, the value of n = 2.
Hence,
Yes!
The solution to the equation is n = 2
-2(7 – n) + 4
What is the answer to this any body know it??????????
Answer:
2n+10
Step-by-step explanation:
you just distribute the -2 and you get -14+2n+4 and then add and you'll get 2n+10
if you are solving for the variable n then you would want your equation like this 2n+10=0
next you would put the 10 on the other side of the equation and have 2n=-10
finally you would divide by 2 and get n=-5
Georgia is able to save $58 a week
from her earnings for babysitting her
neighbor's daughter. How much money
is Georgia able to save in 3 months?
Answer:
She will get $696 from babysitting in 3 months.
Step-by-step explanation:
58x4 = 232. 232x3= $696.
Answer:
696
Step-by-step explanation:
What is f /4 − 24 = −28
Answer: i assume you're looking for F, if so F = -16
Step-by-step explanation:
you would start by adding +24 to each side of the equation, giving you f/4 = -4
then, you would multiply each side of the equation by 4, giving you f = -16
Hue is arranging chairs. She can form 2 rows of a given length with 3 chairs left over, or 5 rows of that same length if she gets 15 more chairs. Complete the equation and solve it to find how many chairs are in that row length. In your equation, use the variable x to represent the number of chairs in each row.
Answer:
X=4
Step-by-step explanation:
2x+3=5x+15
2x-5x=15-3
-3x=12
-3x/-3 = 12/-3
X=4
help me........... .
Answer:
I do not see the question.
Step-by-step explanation:
10 Which shows the factored form of x2 - 12x - 45?
А
(x + 3)(x – 15)
B
(x - 3)(x - 15)
c
(x + 3)(x + 15)
(x - 3)(x + 15)
Answer:
The answer is (x+3)(x-15)
A shop has a sale.
All items are 40% off.
A pair of jeans now cost £24.
How much did they cost before the sale
answer asap ty.!
Thanks
Answer:
x=0
Step-by-step explanation:
5-9+3x = -10+6
-4+3x = -4
+4 . +4 (Both sides)
3x = 0
/3 /3 . (divide both sides by 3)
x=0
solve the triangle. round decimal answers to the nearest 10th.
Answer:
Step-by-step explanation:
m∠A=132°
b≈25.5
c≈18.7
The length of a rectangle is 3 inches less than three times its width. The perimeter of the rectangle is 34 inches. Find the dimensions of the rectangle
Given:
The length of a rectangle is 3 inches less than three times its width.
The perimeter of the rectangle is 34 inches.
To find:
The dimensions of the rectangle.
Solution:
Let x be the width of the rectangle. Then, the length of a rectangle is 3 inches less than three times its width.
Length of the rectangle = 3x-3
Now, perimeter of the rectangle is
[tex]Perimeter=2(Length + Width)[/tex]
[tex]Perimeter=2(3x-3+x)[/tex]
The perimeter of the rectangle is 34 inches.
[tex]34=2(4x-3)[/tex]
[tex]34=8x-6[/tex]
[tex]34+6=8x[/tex]
[tex]40=8x[/tex]
Divide both sides by 8.
[tex]\dfrac{40}{8}=x[/tex]
[tex]5=x[/tex]
The value of x is 5. So, width of the rectangle is 5 inches.
[tex]Length=3x-3[/tex]
[tex]Length=3(5)-3[/tex]
[tex]Length=15-3[/tex]
[tex]Length=12[/tex]
Therefore, the length of the rectangle is 12 inches and the width of the rectangle is 5 inches.
6−3+4x+1= in one solution
Answer:
4x + 4
Step-by-step explanation:
1. 6 - 3 = 3 + 1 = 4
2. You keep the 4x.
3. So 6−3+4x+1= 4x + 4.
Solve expression completely.
64°
O
1
O 64
O Unknown
Answer:
b
Step-by-step explanation:
what is a 2 3/8 divided by 1 and 3/4
***ANSWER PLS***
Chloe was given a box of assorted chocolates for her birthday. Each night, Chloe
treated herself to some chocolates. There were originally 30 chocolates in the box and
after 2 nights, there were 24 chocolates remaining in the box. Write an equation for
C, in terms of t, representing the number of chocolates remaining in the box t days
after Chloe's birthday.
What is C?
Answer:
C=-3t+30
Step-by-step explanation:
C=-3t+30
Your soccer team has won 9 games out of 12 games. You lost 3 out of the 12 games. What is the relative frequency of winning a game? Leave your answer as a percent.
Group of answer choices
75%
25%
1.3%
90%
Answer:
75%
Step-by-step explanation:
9 ÷ 12 = 0.75
0.75 = 75%
have to slove for x
Answer:
x<4
Step-by-step explanation:
Find the missing value pls help need an answer ASAP
Answer:
-7
Step-by-step explanation:
-7 + 5 = -2
Can u mark me brainly pleasee???
Answer:
-7
Step-by-step explanation:
give brainliest jayfeather friend me
Find the GCF of 15 and 16
Answer:
The GCF of 15 and 16 is 1
Step-by-step explanation:
They don't have any other number they are divisible by other than 1
Answer: GCF = 1
Step-by-step explanation:
15=
- 3 x 5
- 1 x 15
16=
- 1 x 16
- 2 x 8
- 4 x 4
Lorne subtracted 6x3 – 2x + 3 from –3x3 + 5x2 + 4x – 7. Use the drop-down menus to identify the steps Lorne used to find the difference.
1. (–3x3 + 5x2 + 4x – 7) + (–6x3 + 2x – 3)
2. (–3x3) + 5x2 + 4x + (–7) + (–6x3) + 2x + (–3)
3. [(–3x3) + (–6x3)] + [4x + 2x] + [(–7) + (–3)] + [5x2]
4. –9x3 + 6x + (–10) + 5x2
5. –9x3 + 5x2 + 6x – 10
Answer:
✔ wrote as addition of the additive inverse
✔ wrote terms as addition of opposite
✔ grouped like terms
✔ combined like terms
Can someone please help me understand how to expand 8(3y-4). Please give a detailed explanation.
Answer:
24y - 32
Step-by-step explanation:
You take the 8 and multiply each term by in the parentheses by 8, so
8(3y - 4) becomes 8 * 3y - 8 * 4 = 24y - 32
Answer:
well, you can multiply them, to simplify the equation, but to expand, try adding or multiplying 2 multiples of 8, in the middle the 4 can change by adding 2+2 or 3+1. For 3y, you can do 3*y.
Step-by-step explanation:
i need help with my math problems
Answer:
Step-by-step explanation:
X Y X Y
0 3 0 5
1 7 1 8
2 11 2 11
3 15 3 14
4 19 4 17
Question 5 Which of these expressions is equivalent to z+z+z+z?
Answer:
well, there is no image but it could be..
4z,z+3z,2z+2z
You have to work on Distributive property 14(5+4)
Work out
a) 4 1/3 × 6
b) 2 3/5 × 3 1/3
Answer:
1. 26
2. 8 2/3
Step-by-step explanation:
4 1/3 x 6 = 13/3 x 6 = 78/3 = 26
2 3/5 x 3 1/3 = 13/5 x 10/3 = 130/15 = 8 2/3
Answer:
41/3 x 6 = 82
2 3/5 x 3 1/3=86.7
Step-by-step explanation:
which graph represents the solution for the following inequality
c < -2
Answer:
I am pretty confident that the answer is the last one
Step-by-step explanation:
I'm not really sure how to explain though lol.
Hope this helps!
A recipe calls for 1 1/2 cups of flour for 1 dozen of cookies. How much flour is needed for 32 cookies?